Mesectodermal Leiomyosarcoma of the Ciliary Body - Park, Sun-Won; Kim, Hyung-Jin; Chin, Hee-Seung; Tae, Kee-Sun; Han, Jee-Young (American Journal of Neuroradiology, 2003)
Summary: We report a case of low-grade mesectodermal leiomyosarcoma of the ciliary body, an extremely rare tumor of neural crest origin, occurring in a 12-year-old boy. MR imaging showed a well-marginated, ovoid soft tissue mass at the right temporal ciliary body, accompanied by total retinal detachment. The mass was slightly hyperintense relative to contralateral vitreous on T1-weighted images and markedly hypointense on T2-weighted images and enhanced very well. Initial biopsy of the mass suggested a peripheral nerve sheath tumor. The mass grew rapidly after biopsy, and enucleation was performed. The final diagnosis based on histology and immunohistochemistry was a low-grade mesectodermal leiomyosarcoma. To our knowledge, this is the first reported case of a malignant form of mesectodermal leiomyoma of the ciliary body.